Analysis of the Arabic Language Skills Curriculum in Arabic Education Department in the Perspective of Common European Framework of Reference for Languages (CEFR) - Zaenuri, Muhammad; Sukirman; Umi Baroroh; Mustofa, Tulus (Asalibuna, 2025)
Abstract: The application of the CEFR in teaching Arabic, especially in non-Arab countries such as Indonesia, remains very limited. This study aims to analyze the compatibility of language proficiency descriptors in the Language Skills course curriculum of the arabic language education department at UIN Raden Mas Said Surakarta with the international CEFR (Common European Framework of Reference for Languages) standards. This research is a literature study to analyze curriculum documents by comparing the competencies and scope of material in the Arabic language skills curriculum in the Arabic language education department at UIN Raden Mas Said Surakarta with the CEFR proficiency level (A1–C2). The results show that the language skills descriptors reflect efforts to develop the four language skills—listening, speaking, reading, and writing—in various contexts, whether in everyday life, professional, or academic. However, most of the competency achievements remain within the range of levels A2 to C1 and have not fully demonstrated the integration between skills as outlined in the CEFR. This study also highlights the importance of adapting the CEFR in Arabic language learning, while maintaining consideration for the social context, culture, national education policy, learner needs, and typical characteristics of the Arabic language. In addition, the integration of intercultural communication competencies in the implementation of the CEFR is key for Arabic language learning to effectively deal with the dynamics of a multilingual and multicultural society.   ملخص: لا يزال تطبيق CEFR في تدريس اللغة العربية، خاصة في البلدان غير العربية مثل إندونيسيا، محدودا للغاية. يهدف هذا البحث لتحليل مدى ملاءمة واصفات الكفاءة اللغوية في  مساق المهارات اللغوية  في منهج قسم  تعليم اللغة العربية في جامعة رادين ماس سعيد سوراكرتا بالمعيار الدولي CEFR (الإطار الأوروبي المرجعي العام للغات). وهذا البحث هو بحث مكتبي لتحليل وثائق المناهج الدراسية من من خلال مراجعة المناهج الدراسية، وخطة التعلم الفصلي (RPS) ، و واصفات مخرجات التعليم في منهج مهارات اللغة العربية في قسم تعليم اللغة العربية في جامعة رادين ماس سعيد الإسلامية الحكومية سوراكرتا مع مستويات الكفاءة اللغوية في الإطار الأوروبي المرجعي العام للغات (A1-C2). تظهر النتائج أن واصف مهارات اللغة قد عكس الجهود المبذولة لتطوير المهارات اللغوية الأربع - الاستماع والكلام والقراءة والكتابة - في سياقات مختلفة، سواء في الحياة اليومية أو المهنية أو الأكاديمية. ومع ذلك، فإن معظم إنجازات الكفاءة لا تزال في حدود المستويات من A2 إلى C1، ولم تثبت بشكل كامل التكامل بين المهارات على النحو المبين في CEFR . يسلط هذا البحث الضوء  على أهمية تكييف CEFR في تعليم اللغة العربية أيضا، مع مراعاة السياق الاجتماعي والثقافة وسياسة التعليم الوطنية واحتياجات المتعلم والخصائص النموذجية للغة العربية. بالإضافة إلى ذلك، يعد دمج كفاءات التواصل بين الثقافات في تنفيذ CEFR أمرا أساسيا لتعليم اللغة العربية للتعامل بفعالية مع ديناميكيات مجتمع متعدد اللغات والثقافات.